Effects of hyperventilation length on muscle sympathetic nerve activity in healthy humans simulating periodic breathing - Spiesshoefer, Jens; Giannoni, Alberto; Borrelli, Chiara; Sciarrone, Paolo; Husstedt, Imke; Emdin, Michele; Passino, Claudio; Kahles, Florian; Dawood, Tye; Regmi, Binaya; Naughton, Matthew; Dreher, Michael; et al. (Frontiers in Physiology, 2022)
Background: Periodic breathing (PB) is a cyclical breathing pattern composed of alternating periods of hyperventilation (hyperpnea, HP) and central apnea (CA). Differences in PB phenotypes mainly reside in HP length. Given that respiration modulates muscle sympathetic nerve activity (MSNA), which decreases during HP and increases during CA, the net effects of PB on MSNA may critically depend on HP length. Objectives: We hypothesized that PB with shorter periods of HP is associated with increased MSNA and decreased heart rate variability (HRV). Methods: 10 healthy participants underwent microelectrode recordings of MSNA from the common peroneal nerve along with non-invasive recording of HRV, blood pressure and respiration. Following a 10-minute period of tidal breathing, participants were asked to simulate PB for 3 minutes following a computed respiratory waveform that emulated two PB patterns, comprising a constant CA of 20 s duration and HP of two different lengths: short (20 s) vs. long (40 s). Results: Compared to (3 minutes of) normal breathing (NB), simulated PB with short HP resulted in a marked increase in mean and maximum MSNA amplitude (from 3.2 ± 0.8 to 3.4 ± 0.8 µV, p=0.04; from 3.8 ± 0.9 to 4.3 ± 1.1 µV, p=0.04, respectively). This was paralleled by an increase in LF/HF ratio of HRV (from 0.9 ± 0.5 to 2.0 ± 1.3; p=0.04). In contrast, MSNA response to simulated PB with long HP did not change as compared to NB. Single CA events consistently resulted in markedly increased MSNA (all p<0.01) when compared to the preceding HPs, while periods of HP, regardless of duration, decreased MSNA (p <0.05) when compared to NB. Conclusions: Overall, the net effects of PB in healthy subjects over time on MSNA are dependent on the relative duration of HP: increased sympathetic outflow is seen during PB with a short but not with a long period of HP